Cholesterol transporters of the START domain protein family in health and disease : START Proteins - Structure and Function - Stocco, Douglas M.; Clark, Barbara J. (Springer New York, 2014)
Non-vesicular intracellular cholesterol transport is an important mechanism for maintaining membrane cholesterol homeostasis. Recent reports of studies directed at soluble cholesterol transport proteins indicate that aberrant expression of the START proteins may contribute to disease states associated with disorders in cholesterol homeostasis. This is an exciting new direction in the field and the purpose of this book will be to highlight the current research directed at potential roles for the START family in diabetes, cancer, and atherogenesis. This book also provides a personal and historical perspective of the discovery-to-publication journey that the authors had for their particular START domain family member. The goal will be to provide perspectives to graduate students, post-doctoral fellows, and endocrinology fellows on the research discovery process.